ANALISIS FAKTOR KERENTANAN INDIVIDU TERHADAP INFEKSI FILARIASIS DI DAERAH KURIPAN KERTOHARJO PEKALONGAN SELATAN - Nurainy, Farah Destyana; Puspitaningrum, Anisa Nova; Alfiyaturrakhma, Untsa (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Filariasis is a chronic infectious disease caused by filarial worm infection and transmitted through mosquito bites as a vector. This disease is still a public health problem in several regions in Indonesia, including in Kuripan Kertoharjo Village, South Pekalongan District, which is an endemic area for filariasis. The purpose of this study was to analyze the factors that influence individual susceptibility to filariasis infection in the region. This study used a quantitative design with a cross-sectional approach. The sample consisted of 100 respondents who were selected purposively based on certain criteria such as domicile, age, and exposure history. Data were collected through structured questionnaires, in-depth interviews, and observations of the environmental conditions of the respondents' homes. The variables studied included demographic factors (age, gender, occupation), individual behavior (use of mosquito nets, habits of going out at night), level of knowledge about filariasis, and environmental conditions (sanitation, presence of puddles, housing density). Data analysis was carried out using the chi-square test and logistic regression to determine the relationship and influence of each variable on infection susceptibility. The results showed that low levels of knowledge, the habit of not using mosquito nets, and poor environmental conditions significantly increased the risk of individuals contracting filariasis (p < 0.05). The conclusion of this study is that susceptibility to filariasis is influenced by the interaction between behavioral factors, knowledge, and environmental conditions. Public health interventions that focus on education, behavioral change, and environmental improvement are needed to reduce the rate of filariasis transmission in endemic areas.